UNBALANCED ENERGY SYSTEM OF UKRAINE AS AN ISSUE OF ENERGY SECURITY - Doronina, Iryna (Collection of scientific papers «ΛΌГOΣ», 2023)
The military conflict on the territory of Ukraine has been ongoing since 2014. Russia annexed Crimea and seized the territories of the Luhansk and Donetsk regions. The analysis of state development strategies and plans for the development of the energy system (2015–2021) showed that the pessimistic scenario of a full-scale military aggression by Russia and, accordingly, an attack on critical infrastructure facilities to ensure the energy security of the country was not foreseen.